2018
DOI: 10.48550/arxiv.1804.06200
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stirling numbers and Gregory coefficients for the factorization of Hermite subdivision operators

Abstract: In this paper we present a factorization framework for Hermite subdivision schemes refining function values and first derivatives, which satisfy a spectral condition of high order. In particular we show that spectral order d allows for d factorizations of the subdivision operator with respect to the Gregory operators: A new sequence of operators we define using Stirling numbers and Gregory coefficients. We further prove that the d-th factorization provides a "convergence from contractivity" method for showing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The paper [24] also shows how to relax the spectral condition, but still retain factorization and convergence results. Furthermore, we recently showed that in general the spectral condition of order d does not imply the reproduction of polynomials up to degree d of the associated scheme [28]. These rather surprising results are the motivation for this paper.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…The paper [24] also shows how to relax the spectral condition, but still retain factorization and convergence results. Furthermore, we recently showed that in general the spectral condition of order d does not imply the reproduction of polynomials up to degree d of the associated scheme [28]. These rather surprising results are the motivation for this paper.…”
Section: Introductionmentioning
confidence: 91%
“…The spectral condition is an important property for the factorizability of an Hermite subdivision scheme [23,28]. Nevertheless, it is known that it is not necessary for the convergence of a scheme [24].…”
Section: Definition 1 (Subdivision Operator) a Subdivision Operator O...mentioning
confidence: 99%
See 3 more Smart Citations